A Comparative Study of Education Equity Policy in Remote Areas in Indonesia and Malaysia - Supianto Supianto; Sri Marmoah; Jenny Indrastoeti Siti Poerwanti; Siti Istiyati; Hasan Mahfud; Sukarno Sukarno (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2023)
This research aims to compare the education equity policies in remote areas of Indonesia and Malaysia to identify the differences, similarities, and effectiveness in addressing socioeconomic disparities between urban and remote regions. The study examines policy documents, government reports, and previous research using a qualitative comparative approach. Indonesia employs a regional autonomy approach, while Malaysia adheres to a centralized system in education policy. Both countries have adopted financial assistance programs to increase the participation of students from low-income families in remote areas. Critical challenges in policy implementation include limited facilities and infrastructure, demanding access to transportation, limited human resources, and sociocultural barriers. The study finds that policy successes are evident in increased student participation, improved infrastructure accessibility, provision of teaching staff, and community support. However, budget constraints and human resource limitations remain significant obstacles. The research concludes that effective education equity policies require proactive government involvement, active community participation, and periodic monitoring and evaluation to enhance policy effectiveness.